2008
DOI: 10.2174/1874473710801010099
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Marijuana Use on Neurocognitive Functioning in Adolescents

Abstract: Marijuana use is common in adolescence, yet neural consequences have not been well delineated. This review seeks to ascertain whether heavy marijuana use in adolescence is associated with persistent neurocognitive abnormalities, and whether adolescents are more vulnerable to the impact of chronic marijuana use than adults.Among heavy marijuana using adults, neurocognitive deficits are apparent for several days following use, but may disappear after one month of abstinence. Studies of adolescent heavy users hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(88 citation statements)
references
References 88 publications
7
79
0
1
Order By: Relevance
“…Even when used separately, these substances appear to create numerous public health problems. For example, marijuana use had the potential of causing structural brain abnormalities and altered neural activity among adolescents, subsequently leading to higher impulsivity and other neurocognitive effects [58,95]. in deviant behaviours [14,27].…”
Section: Discussionmentioning
confidence: 99%
“…Even when used separately, these substances appear to create numerous public health problems. For example, marijuana use had the potential of causing structural brain abnormalities and altered neural activity among adolescents, subsequently leading to higher impulsivity and other neurocognitive effects [58,95]. in deviant behaviours [14,27].…”
Section: Discussionmentioning
confidence: 99%
“…A review by Schweinsburg, Brown, and Tapert (2008a) suggests that while neuropsychological functioning may return after approximately one month of abstinence, adolescent users show deficits up to six weeks after last use. Our lab recently reported a dose-dependent association between past year MJ exposure and poorer sustained attention, psychomotor speed, and cognitive inhibition in emerging adult users ages 18–25 who had been abstinent for an average of 50 days (Lisdahl & Price, 2012).…”
Section: Rationalementioning
confidence: 99%
“…Indeed, converging lines of evidence suggest that chronic use before the age of 17 is associated with deficits in working memory (Schweinsburg et al, 2008, 2010; Becker et al, 2010b), attention (Ehrenreich et al, 1999; Meier et al, 2012; Dougherty et al, 2013), decision-making (Dougherty et al, 2013), visual search (Huestegge et al, 2002), overall and verbal IQ (Pope et al, 1997; Meier et al, 2012), executive functioning (Medina et al, 2009; Becker et al, 2010a; Fontes et al, 2011; Solowij et al, 2012), visuospatial memory (Pope et al, 1997), cognitive inhibition (Fontes et al, 2011), and impulsivity (Dougherty et al, 2013). The magnitude of these deficits is proportional to the frequency, dose, and age at onset of use (Medina et al, 2007a; Schweinsburg et al, 2008, 2010; Becker et al, 2010a; Fontes et al, 2011; Meier et al, 2012). …”
Section: Long-term Effects Of Cannabis Use During Adolescence In Humansmentioning
confidence: 99%
“…In addition, adolescent users of cannabis have reduced cerebral blood flow in the temporal, insular, and PFC regions, and these reductions in blood flow are associated with cognitive deficits (Jacobus et al, 2012). Moreover, converging evidence suggests the presence of abnormal activation patterns in the PFC, limbic region, parietal region, and cerebellum (Schweinsburg et al, 2008; Becker et al, 2010a; Lopez-Larson et al, 2012; Vaidya et al, 2012) in adolescent users of cannabis compared to subjects who do not use cannabis. Interestingly, using diffusion-weighted MRI and connectivity mapping, Zalesky et al (2012) showed that axonal connectivity was impaired in the right fimbria and the corpus callosum, two structures that contain abundant levels of cannabinoid receptors in the developing brain (Romero et al, 1997; Molina-Holgado et al, 2002).…”
Section: Long-term Effects Of Cannabis Use During Adolescence In Humansmentioning
confidence: 99%